A Narrative Database of Major Labor and Product Market Reforms in Advanced Economies - Duval, Romain (IMF Working Papers; Working Paper ;, 2018)
This paper describes a new database of major labor and product market reforms covering 26 advanced economies over the period 1970-2013. The focus is on large changes in product market regulation in seven individual network industries, employment protection legislation for regular and temporary workers, and the replacement rate and duration of unemployment benefits. The main advantage of this dataset is the precise identification of the nature and date of major reforms, which is valuable in many empirical applications. By contrast, the dataset does not attempt to measure and compare policy settings across countries, and as such is no substitute for other publicly available indicators produced, for example, by the ILO, the OECD or the World Bank. It should also be seen as work in progress, for researchers to build on and improve upon. Based on the dataset, major reforms appear to have been more frequent in product markets than in labor markets in the last decades, and were predominantly implemented during the 1990s and 2000s.